“elaboración de barras de aleaciones especiales por centrifugación bajo norma astm - Villacis Montaño, Juan Fernando (2009)
It keeps a process about simulation in order to solidify under pressure an aluminum alloy and carry out parameters of solidification about centrifugation, this is a process that depends on pressure so that we can figure out the number G which must spin the mold in order to develop a lot of nucleation cores which fine the structure and generate higher mechanical stresses.